Cognitive flexibility, impulsivity, and compulsivity in problematic consumption behaviours - María Jara-Rizzo; Daniel Oleas; Jose A. Rodas (PLoS ONE, 2026)
Different studies have identified cognitive inflexibility, impulsivity and compulsivity in substance use and gambling disorder, but it is unclear whether these deficits are present in other possible addictive behaviours. In this study, we evaluated cognitive inflexibility, as measured by the Probabilistic Reversal Learning Task (PRLT), impulsivity across UPPS-P model and the compulsivity in regular gamblers, buyers, video gamers, consumers of pornography and control group. Multivariate analysis was performed to evaluate the five groups, revealing higher scores across several impulsivity and compulsivity domains in the buyers group compared to the other groups. On the overall measure of cognitive flexibility using the PRLT, buyers performed worse than gamers and pornography users, suggesting a relative disadvantage in adapting to changing reward contingencies even before trial-level learning patterns were examined. To further evaluate patterns of cognitive flexibility across groups, a GLME model was developed. The results showed that phase-group interactions were generally weak, and none of the contrasts related to reversal differed between groups. This indicates that the cost of adapting to contingency reversals was similar across all five groups, with no evidence that any particular group would exhibit greater inflexibility during reversal phases. Finally, the findings show that impulsivity and compulsivity can manifest themselves differently in these activities, which has implications for the development of more personalised intervention strategies that take into account both the nature of the disorder and the specific cognitive deficits involved.